The challenge of Christian higher education on the African continent in the twenty-first century - Van der Walt, B. J. (Christian Higher Education, 2002)
This article consists of three main sections. In the first, reasons are given why a vision for Christian higher education is, to a large degree, still lacking in Africa. The following factors are dealt with to explain this situation: (1) the politicaleconomic- social environment; (2) the character of Christianity on the continent; (3) the state of higher education; and (4) the implications of all these factors for Christian higher education. The second main section develops a basis for a vision for Christian higher education by listening to what Romans 12:2 says about the renewing of our minds. The final section provides an answer to the question how this vision for Christian education could be realized in Africa. A proposal is made for the establishment of an African Center for Christian Higher Education. How this could be done, and what its key activities should be are spelled out in a practical way.
Paid